Calculation of road accessibility for the rural population in the Shikoku Island of Japan using GIS. (13th November 2019) - Katayama, R; Defratti, M; Inoue, T; Peters, L
Abstract: Background: The United Nations has defined 17 Sustainable Development Goals as a blueprint for helping ensure the health and well-being of our world by 2030. The global goals address challenges we face including poverty, inequality, climate, environmental, peace and prosperity. The goals each have targets and indicators to help measure success. Indicator #9.1.1 is defined as "Proportion of the rural population who live within 2 km of an all-season road", which can aid in understanding multiple areas of human well-being including access to food, health care, education and in support of economic development. By understanding access to infrastructure, we can focus on affordable and equitable access for all. We focused on the Shikoku Island of Japan and calculated indicator #9.1.1 using spatial analysis. Methods: We utilized data from three sources listed below. Cho-cho-moku boundaries population data from the Esri Japan corporation. Metropolitan Employment Area data from the Center for Spatial Information Science at the University of Tokyo. Emergency transport road data from the MLIT of Japan. We conducted proximity analysis with Geographic Information System (GIS) and estimated population of the target area using the area ratio of the target area to the original Cho-cho-moku area. Results: The percentage of the rural population who live within 2 km of an all-season road is 79.5% and those who have no access to an all-season road in the Shikoku Island is 20.5%. Conclusions: We found the proportion of the rural population that cannot reach an all-season road by calculating indicator #9.1.1. 20.5% of the rural population in the Shikoku Island of Japan may have difficulties accessing essential services such as health care, education, food, and may have difficulties with economic development. By understanding accessibility to road infrastructure, we were able to identify areas at risk for access. We can work towards creating more equitable access in a next step. Key messages: By conducting spatial analysis with GIS, we can identify areas at risk for access to infrastructure. we can focus on creating more affordable and equitable access for all by understanding access to infrastructure such as health care, education and food.